The Effects of the U.S. Income Tax Regulations' Transfer Pricing Rules on Allocative Efficiency . - Halperin, Robert; Srinidhi, Bin (The Accounting Review, 1987)
ABSTRACT: The two most commonly used transfer pricing rules for tax purposes pursuant to Reg. Sec. 1.482 are the "resale price" method and the "cost plus" method. This paper analyzes the effects of each of these methods on the resource allocation decisions of multinational firms when the tax rate abroad is lower than in the U.S. We show that, relative to the resource allocation that would exist in the absence of taxation: (1) the resale price method can cause either an increase or decrease in imports, an overuse of domestic resources, and overproduction of the "most similar product"; and (2) the cost plus method causes a decrease in imports, a decrease in the use of domestic resources, and overproduction of the most similar product. These effects are reversed when the tax rate abroad is higher than in the U.S. In addition, we deal with the case where the MNE faces different transfer pricing regulations in the U.S. and the foreign country.